Tropical rain forest recovery after cyclone and human activity on Savai'i, Samoa : a field study of tree species composition and distribution - Netterling, Sakura (SLU/Dept. of Forest Ecology and Management, 2008)
This MFS study was conducted in the island of Savai'i of State Samoa, performed as a follow up to a ten years previous study. The aim was to estimate the recovery of forest species diversity following two sequential cyclones that passed over the forest reserve of Tafua-Tai 1990 and 1991. We compared this natural disturbance to a cumulative natural disturbance as an extensive area suffered from a fire one month after the cyclone 'Ofa'. To broaden the work and to include a forestry aspect a comparison of human afflicted disturbance a survey was made in the area near Taga village. Here a substantial area had been clear-felled in the same time interval as the cyclones, and one harvested and logged just five years ago. We performed relative abundance analysis and compared the status of the forests as well as climber and vines ratio between the disturbance regimes. It was found that cumulative disturbance severely affected the area and opened it up to secondary forest species and vines which arrest crown growth. The severest damage was still found in the clear-felled area that during the fifteen years interval has not recovered and was significantly worse in all aspects to the other disturbed areas. One can interpret that the logged and harvested area which was five years old was as good as the cumulative natural disturbance area due to a more selective logging. However, both are still not as diverse and some of the most important mature forest species are missing. Invasive species such as Funtumia elastica, a shadow tolerant exotic species and a late introduction, show an alarming dominance in the naturally disturbed area.